Overcoming water scarcity and quality constraints: Overview - Meinzen-Dick, Ruth S.; Rosegrant, Mark W. (International Food Policy Research Institute, 2001)
Access to enough water of sufficient quality is fundamental for all human, animal, and plant life as well as for most economic activity. At the global level, plenty of water is available. But to meet the demand, water has to be supplied where and when it is needed.